1999
DOI: 10.1029/1999jd900404
|View full text |Cite
|
Sign up to set email alerts
|

A barrier to vertical mixing at 14 km in the tropics: Evidence from ozonesondes and aircraft measurements

Abstract: Abstract. We use ozonesondes launched from Samoa (14øS) during the Pacific Exploratory Mission (PEM) Tropics A to show that O3 mixing ratios usually start increasing toward stratospheric values near 14 km. This is well below the tropical tropopause (as defined either in terms of lapse rate or cold point), which usually occurs between 16 and 17 km. We argue that the main reason for this discrepancy in height between the chemopause and tropopause is that there is very little convective detrainment of ozone-deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
256
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(285 citation statements)
references
References 16 publications
26
256
0
Order By: Relevance
“…These cloud levels are more than 100 hPa below the tropopause, which is located around 100 hPa in the tropics. This is in agreement with other studies that suggest that most convective cloud tops do not extend up to the tropopause, but to the bottom of the tropical transition layer (Folkins et al, 1999;Fueglistaler et al, 2009), several kilometres below the tropopause. Furthermore, the effective (also called optical centroid) cloud pressure derived from VIS and NIR (oxygen A-band) satellite measurements using the Lambertian cloud model lies well below the physical cloud top pressure (Joiner et al, 2012;Ziemke et al, 2009a).…”
Section: Cloud Propertiessupporting
confidence: 93%
“…These cloud levels are more than 100 hPa below the tropopause, which is located around 100 hPa in the tropics. This is in agreement with other studies that suggest that most convective cloud tops do not extend up to the tropopause, but to the bottom of the tropical transition layer (Folkins et al, 1999;Fueglistaler et al, 2009), several kilometres below the tropopause. Furthermore, the effective (also called optical centroid) cloud pressure derived from VIS and NIR (oxygen A-band) satellite measurements using the Lambertian cloud model lies well below the physical cloud top pressure (Joiner et al, 2012;Ziemke et al, 2009a).…”
Section: Cloud Propertiessupporting
confidence: 93%
“…In agreement with typical q E values in the tropical MBL [Folkins et al, 1999], the present observations show values of $354 -357 K outside the downdraft regime for these two days of measurements (Figure 4).…”
Section: Convective Downdrafts During 18-19 September 2002supporting
confidence: 75%
“…Surface sensible and latent heat fluxes are considered the main sources of q E in the atmosphere [Betts et al, 1992], while the primary sink is radiative cooling of the troposphere. Consequently, the tropical lower troposphere is characterized by a decrease in q E and an increase in O 3 with height [Folkins et al, 1999;Zachariasse et al, 2000;Betts et al, 2002]. Independent meteorological parameters such as temperature and pressure may not be conserved in downdrafts, while q E is near conservative.…”
Section: Convective Downdrafts During 18-19 September 2002mentioning
confidence: 99%
“…This exchange is related to Rossby wave mixing, which is ultimately correlated with monsoonal circulations. Further, Folkins et al [1999] among others, have identified in the tropics a region, below the tropopause and above 14 km, which contains air with stratospheric ozone, suggesting a mixed region between the troposphere and the stratosphere at low latitudes. In total, current observations point to a need to reconsider the traditional concepts used to describe the mechanisms of stratosphere-troposphere exchange.…”
Section: Discussionmentioning
confidence: 99%